Estudo exploratório de processos de transformação sonora a partir de Trevor Wishart: reinvenção e tradução para o ambiente SuperCollider - Fellipe Miranda Martins (2020)
The creative practice of transforming recorded sounds has its origins on the works by Pierre Schaeffer and the Groupe de Recherches Musicales (GRM), however, this practice acquires a new dimension with the development of the computer programs suite Composers Desktop Project (CDP) – headed by the English composer, performer and developer Trevor Wishart. Although CDP’s programs were primely designed for non-real-time execution, the audio programming environment SuperCollider – which is mainly centered at real time logic – features flexibility not only for porting these processes but also allows and facilitates the creation of new correlated ones. Two main sound transformation types were analyzed, those in which the computer calculations were realized on the time domain – using the wavesets idea – and those in which calculations were realized on the spectral domain – using the data from the phase vocoder. In this work, CDP’s time and spectral transformations are revisited under the light of the new possibilities brought by the SuperCollider and the auditory evaluation of source and transformed sounds. At last, new transformations and expanded variants are proposed in the format of small sound studies, demonstrating how these procedures have been incorporated and integrated into the creative practices by the author of the present text.